Joint demeanors of an anthropomorphic robot in designing the novel walking gait - ., Md. Akhtaruzzaman; Shafie, Amir Akramin (2011)
The movement patterns of various joint actuators of the humanoid system are described in this paper to identify and understand the behavior of the biped walking motions. This paper focuses on two major parts of the study, firstly the analysis and design of human like walking gait for an anthropoid system and secondly the implementation of the designed gait to navigate the robot from a source position to a destination point. The walking strategy is demonstrated on a flat surface where the robot performs its tasks without losing its upright position. The perfect combination of actuator motions determines the robustness of the humanoid system where the angular positions are established through the Inverse Kinematics analysis depending on the geometrical and trigonometric formulation. The paper mainly represents the joint demeanors of the humanoid robot in performing the designed walking gait.